E-070 Endovascular Techniques for Achievement of Better Flow Diverter Wall Apposition. (29th July 2016) - Kuhn, A; de Macedo Rodrigues, K; Gounis, M; Kan, P; Marosfoi, M; Lozano, J; Perras, M; Brooks, C; Howk, M; Rex, D; Massari, F; Wakhloo, A; et al.
Abstract : Purpose: Flow diverter malapposition as a technical complication with the use of the pipeline embolization device has been described and maybe is associated with delayed ischemic events or potentially delayed life-threatening aneurysm rupture. We describe our endovascular techniques for manipulation of flow diverters in order to achieve proper vessel wall apposition. Materials and methods: We retrospectively analyzed our flow diverter database and included all patients in whom malapposition of the device was detected on follow-up angiography immediately after device deployment. We then evaluated feasibility and technical success of different endovascular approaches aimed to correct the inadequate vessel wall apposition. Successful endovascular techniques for manipulation of the device included use of wires, catheters and additional devices. Final confirmation of flow diverter wall apposition prior to completion of the intervention was performed using 3D multi-planar cone-beam CT reconstruction images. Results: We identified 5 successful endovascular techniques for better flow diverter wall apposition: 1) Use of a wire with a J, pigtail or S-shaped tip passed through the device, 2) Manipulation with a microcatheter, which can be used to press the PED against the vessel wall, 3) Balloon angioplasty of the malapposed segment, 4) Manipulation with an intermediate catheter, which can be used at the proximal edge or within the flow diverter to push the PED against the vessel wall, 5) Placement of another flow diverter within the previously placed FD to better oppose the ends and 6) Placement of an open-cell stent in telescopic fashion across the malapposed portion of the PED (proximal or distal edge). The Neuroform stent with its high outward radial force is an excellent adjunct treatment option to anchor the malapposed flow diverter against the vessel wall while permitting perforator patency. Conclusion: Flow diverter malapposition can be addressed successfully during the interventional procedure using a variety of techniques. This may prevent devastating delayed complications. Disclosures: A. Kuhn: None. K. de Macedo Rodrigues: None. M. Gounis: 1; C; NIH, Medtronic Neurovascular, Microvention/Terumo, Cerevasc LLC, Gentuity, Codman Neurovascular, Philips Healthcare, Stryker Neurovascular, Tay Sachs Foundation, and InNeuroCo Inc. 2; C; Codman Neurovascular and Stryker Neurovascular. 4; C; InNeuroCo Inc. P. Kan: 2; C; Stryker Neurovascular, Covidien, and MicroVention. M. Marosfoi: None. J. Lozano: None. M. Perras: None. C. Brooks: None. M. Howk: None. D. Rex: None. F. Massari: None. A. Wakhloo: 1; C; NIH, Philips Healthcare, Wyss Institute. 2; C; Codman Neurovascular and Stryker Neurovascular. 3; C; Harvard Postgraduate Course, Miami Cardiovascular Institute. 4; C; InNeuroCo Inc, EpiEB and Pulsar Medical. A. Puri: 1; C; Stryker Neurovascular and Covidien. 2; C; Codman Neurovascular, Stryker Neurovascular and Covidien. 3; C; Miami Cardiovascular Institute. 4; C; InNeuroCo Inc.